Cartilage oligomeric matrix protein is a novel notch ligand driving embryonic stem cell differentiation towards the smooth muscle lineage. (August 2018) - Ma, Baihui; Yao, Fang; Xie, Nan; Mao, Chenfeng; Liu, Fei; Gong, Ze; Zhao, Guizhen; Liu, Zhujiang; Cai, Zeyu; Yu, Fang; Dai, Rongbo; Chen, Zhongjiang; et al.
Abstract: Cartilage oligomeric matrix protein (COMP), a protective component of vascular extracellular matrix (ECM), maintains the homeostasis of mature vascular smooth muscle cells (VSMCs). However, whether COMP modulates the differentiation of stem cells towards the smooth muscle lineage is still elusive. Firstly, purified mouse COMP directly induced mouse embryonic stem cell (ESC) differentiation into VSMCs both in vitro and in vivo, while the silencing of endogenous COMP markedly inhibited ESC-VSMC differentiation. RNA-Sequencing revealed that Notch signaling was significantly activated by COMP during ESC-VSMC differentiation, whereas the inhibition of Notch signaling attenuated COMP-directed ESC-VSMC differentiation. Furthermore, COMP deficiency inhibited Notch activation and VSMC differentiation in mice. Through silencing distinct Notch receptors, we identified that Notch1 mainly mediated COMP-initiated ESC-VSMC differentiation. Mechanistically, COMP N-terminus directly interacted with the EGF11-12 domain of Notch1 and activated Notch1 signaling, as evidenced by co-immunoprecipitation and mammalian two-hybrid assay. In conclusion, COMP served as a potential ligand of Notch1, thereby driving ESC-VSMC differentiation. Highlights: COMP guides ESC-VSMC differentiation dependent on Notch1 activation. COMP directly activates Notch1 signaling. COMP N-terminus directly interacts with the EGF11–12 domain of Notch1.